2007
DOI: 10.1111/j.1467-7652.2007.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

A potato carboxypeptidase inhibitor gene provides pathogen resistance in transgenic rice

Abstract: SummaryA defensive role against insect attack has been traditionally attributed to plant protease inhibitors. Here, evidence is described of the potential of a plant protease inhibitor, the potato carboxypeptidase inhibitor (PCI), to provide resistance to fungal pathogens when This fungal carboxypeptidase was found to be a novel carboxypeptidase B which was fully inhibited by PCI. Overall, the results indicate that PCI exerts its antifungal activity through the inhibition of this particular fungal carboxypepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 68 publications
(87 reference statements)
0
34
0
1
Order By: Relevance
“…Together, disease resistance assays demonstrated that expression of the mpi‐pci fusion gene in rice, either the mpi‐2A‐pci or the mpi‐C‐pci gene, confers enhanced resistance against the rice blast fungus M. oryzae . Furthermore, these results indicated that the MPI‐C‐PCI fusion protein might be effective for inhibition of fungal proteinases (as it was previously demonstrated for PCI; Quilis et al ., ). Knowing that the fusion protein is partially processed in rice leaves of mpi‐2A‐pci (see Figure a), the contribution to the phenotype of disease resistance that is observed in these plants might be due to the activity of the MPI‐2A‐PCI protein and the PCI protein originating from the fusion protein.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Together, disease resistance assays demonstrated that expression of the mpi‐pci fusion gene in rice, either the mpi‐2A‐pci or the mpi‐C‐pci gene, confers enhanced resistance against the rice blast fungus M. oryzae . Furthermore, these results indicated that the MPI‐C‐PCI fusion protein might be effective for inhibition of fungal proteinases (as it was previously demonstrated for PCI; Quilis et al ., ). Knowing that the fusion protein is partially processed in rice leaves of mpi‐2A‐pci (see Figure a), the contribution to the phenotype of disease resistance that is observed in these plants might be due to the activity of the MPI‐2A‐PCI protein and the PCI protein originating from the fusion protein.…”
Section: Resultsmentioning
confidence: 97%
“…(b) Affinity chromatography on immobilized CPA of pure PCI (Sigma) and protein extracts from rice plants constitutively expressing pci (line 7.34) , mpi‐C‐pci plants (line 7) and mpi‐2A‐pci (line 7) plants. Eluted fractions were analysed for inhibition of bovine CPA activity using AAFP as the substrate (Quilis et al ., ). Lanes E1a to E1c, fractions eluted using buffer at pH 9.0.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The gene size and coding regions of these inhibitors are small, devoid of introns (Wang et al 2008) and comprise readily identifiable core region covering the invariant cysteine residues. The potential of PI has been demonstrated by the transfer of these genes from different sources to several plants of economic interest, resulting in transgenic plants more resistant to predation (Lingling et al 2005; Pujol et al 2005) and pathogens (Qu et al 2003; Quilis et al 2007). …”
Section: Introductionmentioning
confidence: 99%